1983
DOI: 10.1128/jb.153.2.867-871.1983
|View full text |Cite
|
Sign up to set email alerts
|

Energy coupling to nitrite respiration in the sulfate-reducing bacterium Desulfovibrio gigas

Abstract: By use of a membrane fraction prepared from Desulfovibrio gigas grown in a lactate-sulfate medium, synthesis of ATP was demonstrated to be coupled to the oxidation of molecular hydrogen and reduction of either nitrite or hydroxylamine. This phosphorylation was uncoupled from electron transport by pentachlorophenol, methyl viologen, and gramicidin, but not by oligomycin. The extrusion of protons from the cells was shown to be coupled to the hydrogen-nitrite respiratory system, and, assuming the localization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 27 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The finding that the NrfH menaquinol‐binding site is at the membrane–periplasm interface confirms predictions that electron transport through the NrfH cytochromes is electroneutral and not associated with energy conservation (Simon, 2002), as the protons generated upon oxidation of menaquinol are most likely released directly to the periplasm. This finding is of no relevance to the metabolism of D. vulgaris , which only uses NrfHA to detoxify nitrite, but is important for other Desulfovibrio spp like D. gigas and D. desulfuricans , which grow by respiratory nitrite ammonification with H 2 or formate (Steenkamp and Peck, 1981; Barton et al , 1983). In this growth mode, a proton‐motive force has to be generated upon reduction of menaquinone by either H 2 or formate.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that the NrfH menaquinol‐binding site is at the membrane–periplasm interface confirms predictions that electron transport through the NrfH cytochromes is electroneutral and not associated with energy conservation (Simon, 2002), as the protons generated upon oxidation of menaquinol are most likely released directly to the periplasm. This finding is of no relevance to the metabolism of D. vulgaris , which only uses NrfHA to detoxify nitrite, but is important for other Desulfovibrio spp like D. gigas and D. desulfuricans , which grow by respiratory nitrite ammonification with H 2 or formate (Steenkamp and Peck, 1981; Barton et al , 1983). In this growth mode, a proton‐motive force has to be generated upon reduction of menaquinone by either H 2 or formate.…”
Section: Resultsmentioning
confidence: 99%
“…Although the differences in the initial rates of nitrate and nitrite reduction should be considered, the factors determining nitrite accumulation still remain uncer-tain. Accumulation of ammonia could be attributed to other metabolic pathways related to sulphide oxidation and nitrate reduction such as DNRA (Dissimilatory Nitrate Reduction to Ammonia) which is performed by a number of facultative anaerobic bacteria such as Desulfouibrio gigas [23]. A more detailed review on this subject can be found in [24].…”
Section: Discussionmentioning
confidence: 99%
“…Many strains of sulfate reducing bacteria such as Desulfovibrio vulgaris that have been isolated from natural environments outside warm blooded animals lack genes for nitrate reduction, but with few exceptions, they are able to reduce nitrite to ammonia 1 8 . Nitrite reduction is catalysed by the periplasmic NrfHA nitrite reductase 4 , 9 – 11 .…”
Section: Introductionmentioning
confidence: 99%